2015
DOI: 10.15448/1980-6108.2015.1.19688
|View full text |Cite
|
Sign up to set email alerts
|

Características biomecânicas dos pés no período gravídico-puerperal: estudo de caso

Abstract: 2 Professor(a) doutor(a) do Programa de Pós-Graduação em Fisioterapia da UDESC, Florianópolis, SC. RESUMOObjetivos: Avaliar as variações antropométricas e a distribuição de pressão plantar dos pés durante o ciclo gravídico-puerperal de uma paciente. Descrição do caso: Este estudo descritivo-exploratório analisou uma gestante por meio de oito avaliações, seis durante a gestação (na 26ª, 28ª, 30ª, 32ª, 34ª e 36ª semana da gestação) e duas no puerpério (10º e 50º dia após o parto). Foram avaliadas seis variáveis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This analysis suggests that in the third trimester, the plantar arch height is lower than in the first trimester and in the puerperium. This is in line with published findings according to which the height of the arch of the foot tends to decrease in both feet [ 12 , 25 , 31 ]. In this respect, some studies have even observed a degree of permanence in these changes after delivery [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…This analysis suggests that in the third trimester, the plantar arch height is lower than in the first trimester and in the puerperium. This is in line with published findings according to which the height of the arch of the foot tends to decrease in both feet [ 12 , 25 , 31 ]. In this respect, some studies have even observed a degree of permanence in these changes after delivery [ 25 ].…”
Section: Discussionsupporting
confidence: 93%